Mejoramiento de la producción de miel de abeja nativa sin aguijón en el departamento de Loreto - Delgado Vásquez, Cesar Augusto (2024)
The production of stingless bee honey in the department of Loreto is low, the objective of this study is to improve the production in volume and quality of honey from stingless bees. The study was carried out from May 2019 to April 2023, in the communities of Chingana and San Francisco in the department of Loreto. Experiments were established to compare the volume of production of honey in a rational box and in an artisanal way per year, the physical-chemical characterization of honey was carried out, and the plant species used by stingless bees as a source of food, resins, and nesting habitat, and the main pests of bees were identified. The volume of honey production per year in rational boxes was higher than that produced in an artisanal way, the humidity and sugar parameters are outside the limits established by the Codex Alimentarius, stingless bees most frequently use the Fabaceae and Myrtaceae families as a food source, the Hypericaceae and Anacardiaceae as a source of resin, and the Rubiaceae family with the species Calycophyllum spruceanum as nesting habitat. The black fly Pseudohypocera kerteszi has been recorded as the main pest for hives. It is concluded that the production of stingless honey has improved its performance, and it is considered necessary to create a Technical Standard for stingless honey.